2015
DOI: 10.1182/blood-2014-04-567024
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of concomitant Jak2V617F expression and Tet2 loss in mice promote disease progression in myeloproliferative neoplasms

Abstract: Key Points Tet2 loss of function confers a strong functional competitive advantage to Jak2V617F-mutant hematopoietic stem cells. Jak2V617F expression and Tet2 loss generate distinct and nonoverlapping transcriptional programs in hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 42 publications
(55 reference statements)
8
80
1
1
Order By: Relevance
“…Overall changes were subtle and Tet2 loss led mainly to an increased self-renewal signature. 1 In the model of Kameda et al, 2 Jak2V617F decreased this self-renewal signature, and the combined loss of Tet2 only partially restored it, in agreement with what they observed in their mouse model. The precise mechanism by which TET2 loss increases self-renewal capacities of HSCs is still poorly known.…”
Section: William Vainchenker and Isabelle Plo Institut De Cancérologisupporting
confidence: 79%
See 2 more Smart Citations
“…Overall changes were subtle and Tet2 loss led mainly to an increased self-renewal signature. 1 In the model of Kameda et al, 2 Jak2V617F decreased this self-renewal signature, and the combined loss of Tet2 only partially restored it, in agreement with what they observed in their mouse model. The precise mechanism by which TET2 loss increases self-renewal capacities of HSCs is still poorly known.…”
Section: William Vainchenker and Isabelle Plo Institut De Cancérologisupporting
confidence: 79%
“…In about 6% of those cases, mutations in the TET2 gene are found even in the absence of any hematologic disorder, demonstrating that TET2 mutations are capable of giving rise to a clonal hematopoiesis, possibly favoring secondarily the occurrence of the JAK2V617F mutation. 9 In the 2 present studies, the authors directly demonstrate that TET2 loss is capable of completely 1 However, the effects of Tet2 loss were not restricted to HSCs but also led to a more severe MPN in mice and accelerated death compared to the single Jak2V617F mutation in the absence of leukemia occurrence. One of the most striking differences is the increased extramedullary hematopoiesis as revealed by a massive splenomegaly in the double-mutant mice.…”
Section: William Vainchenker and Isabelle Plo Institut De Cancérologimentioning
confidence: 50%
See 1 more Smart Citation
“…The pathogenetic role of these other mutations is incompletely understood and might include cooperation with the driver mutations in facilitating disease progression [49,50]. Specific genes affected in this regard include those relevant to epigenetic (e.g., ASXL1, TET2, EZH2, IDH1, IDH2, DNMT3A), RNA splicing (e.g., SRSF2, U2AF1, SF3B1) or transcriptional (TP53, IKZF1, NF-E2, CUX1) regulation.…”
Section: Pathogenetic Contribution Of Mutations In Myeloproliferativementioning
confidence: 99%
“…In addition, combined Tet2 loss with AML1-ETO leads to fully penetrant AML in vivo, partially due to hypermethylation of enhancer regions thereby silencing tumor suppressors [59,75]. Furthermore, studies from two independent groups have shown that combination of Tet2 loss and Jak2V617F resulted in aggressive MPN phenotype through both clonal HSC dominance and expansion of downstream precursor populations [76,77]. Notably, TET2 mutations also cooccur with changes in other TET members or DNMT3A mutations in human acute B-lymphocytic leukemia and T-cell lymphoma [78,79].…”
Section: Tet2mentioning
confidence: 99%